2022
DOI: 10.1073/pnas.2202104119
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous pannexin1 channels form functional intercellular cell–cell channels with characteristic voltage-dependent properties

Abstract: Significance Pannexin1 is a glycoprotein that has been shown to form functional plasma membrane channels and mediate many cellular signaling pathways. However, the formation and function of pannexin1-based intercellular cell–cell channels in mammalian cells and vertebrate tissue is a question of substantial debate. This work provides robust electrophysiological evidence to demonstrate that endogenously expressed human pannexin1 forms cell–cell channels and lays the groundwork for studying a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…Of note, recordings were conducted in symmetrical conditions, that is, using internal recording solutions (with high K + ) in both the cell attached patch and whole cell pipettes, arguing against an effect of high [K] o on inducing Px1 HC openings of large conductance (300-500 pS). Our data call for caution regarding the extrapolation of various Px1 HC configurations from dual whole cell recordings from pairs of electrically coupled cells via Px1 GJ channels (Palacios-Prado et al, 2022). In these recordings, a whole cell pipette monitors whole cell channel activity including that of Px1 GJ channels and unopposed Px1 HCs, and analysis of both unitary activities may be challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, recordings were conducted in symmetrical conditions, that is, using internal recording solutions (with high K + ) in both the cell attached patch and whole cell pipettes, arguing against an effect of high [K] o on inducing Px1 HC openings of large conductance (300-500 pS). Our data call for caution regarding the extrapolation of various Px1 HC configurations from dual whole cell recordings from pairs of electrically coupled cells via Px1 GJ channels (Palacios-Prado et al, 2022). In these recordings, a whole cell pipette monitors whole cell channel activity including that of Px1 GJ channels and unopposed Px1 HCs, and analysis of both unitary activities may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the unitary conductance of Cx43 HCs is about 220 pS, twice that of the gap junction channels, ~110 pS (Bukauskas et al, 2001; Bukauskas & Peracchia, 1997; Contreras et al, 2003). In contrast to Cx43 GJ, Px1 GJ channels may open with two main conductances, a prevalent voltage‐sensitive state of ~35 pS, and an infrequent and voltage‐insensitive state of ~170 pS (Palacios‐Prado et al, 2022). While early studies reported that when expressed exogenously in oocytes, human Px1 forms unopposed HCs that open with a maximum unitary conductance of ~500 pS (Bao et al, 2004; Qiu & Dahl, 2009), others have found that Px1 HCs have unitary conductances no larger than ~100 pS in excised outside out and inside out patches (Chiu et al, 2017; Ma et al, 2012), and there is still no general agreement on the single channel conductance of vertebrate unopposed Px1 HCs in the whole cell.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been reported to contribute to the intracellular Ca 2+ homeostasis ( Shestopalov and Panchin, 2008 ). This single-membrane channel dogma was recently challenged by Palacios-Prado et al (2022) showing electrophysiological recordings of Panx1-mediated GJ-like direct cell-cell communication in transfected HeLa cells and in a human oligodendroglioma cell line naturally expressing Panx1. Whether primary cells and other cell lines show similar properties remains to be proven in the coming years.…”
Section: The Pannexin Protein Familymentioning
confidence: 99%
“…However, when the N-linked glycosylation site is altered, preventing this post-translational modification, structural biology data suggests gap junction formation is possible [ 125 ]. One recent article argued that gap junction-forming innexins contain N-glycosylation sites at their extracellular loops and could form gap junction types of channels [ 126 ]. Using TC620 cells, an oligodendroglioma cell line, dye and electrical cell coupling were shown; the cell-to-cell coupling was reduced when Panx-1 was either knocked down by siRNA or inhibited by an inhibitory peptide [ 126 ].…”
Section: Hiv and Panx-1 Interactionsmentioning
confidence: 99%
“…One recent article argued that gap junction-forming innexins contain N-glycosylation sites at their extracellular loops and could form gap junction types of channels [ 126 ]. Using TC620 cells, an oligodendroglioma cell line, dye and electrical cell coupling were shown; the cell-to-cell coupling was reduced when Panx-1 was either knocked down by siRNA or inhibited by an inhibitory peptide [ 126 ]. However, Panx-1′s capacity to form gap junctions is still an open question.…”
Section: Hiv and Panx-1 Interactionsmentioning
confidence: 99%